Integrating cover crops for weed management in the semiarid U.S. Great Plains: opportunities and challenges. Issue 4 (16th July 2020) - Kumar, Vipan; Obour, Augustine; Jha, Prashant; Liu, Rui; Manuchehri, Misha R.; Dille, J. Anita; Holman, John; Stahlman, Phillip W.
Abstract: The widespread evolution of herbicide resistance in weed populations has become an increasing concern for no-tillage (NT) growers in semiarid regions of the U.S. Great Plains. Lack of cost-effective and alternative new herbicide sites of action further exacerbates the problem of herbicide-resistant (HR) weeds and threatens the long-term sustainability of prevailing cropping systems in the region. A recent decline in commodity prices and increasing herbicide costs to manage HR weeds has spurred research efforts to build a strong rationale for developing ecologically based integrated weed management (IWM) strategies in the U.S. Great Plains. Integration of cover crops (CCs) in NT dryland production systems potentially offers several ecosystem services, including weed control, soil health improvement, decline in selective pest pressure, and overall reduction in pest management inputs. This review article aims to document the role of CCs for IWM, with emphasis on exploring emerging weed issues; ecological, economic, and agronomic benefits of growing CCs; and constraints preventing adoption of CCs in NT cropping systems in the semiarid Great Plains. We attempt to focus on changes in weed management practices, their long-term impacts on weed seedbanks, weed shifts, and herbicide-resistance evolution in the most common weed species in the region. We also highlight current knowledge gaps and propose new research priorities based on an improved understanding of CC management strategies that will ultimately aid in achieving sustainable weed management goals and preserving natural resources in water-limited environments.